Implementasi Peraturan Walikota Nomor 7 Tahun 2020 Tentang Pembentukan Gugus Tugas Percepatan Penanganan Covid-19 di Kota Ternate - Muslah, Muhammad; Salam, Rahmat; Yusuf , Syandra; Kasim, Sukarman; Muksin, Nani Nurani (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
Implementation Of Mayor Regulation Number 7 Of 2020 Concerning The Formation Of A Task Force To Accelerate Handling Of Covid – 19 In Ternate City. This study aims to determine and understand the Implementation of Ternate Mayor Regulation No. 7 of 2020 concerning the Establishment of a Task Force for the Acceleration of Emergency Handling of Corona Virus Disease (Covid-19) in Ternate City. The method in this study is a qualitative method so that it produces descriptive data obtained from in-depth interviews with informants. There are several stages used in analyzing data, namely data reduction, data presentation, and the conclusion drawing stage. The results of the study indicate that the cause of the poor implementation of Ternate Mayor Regulation No. 7 of 2020 concerning the Establishment of a Task Force for Emergency Handling of Corona Virus Disease (Covid) is due to the large number of Ternate City residents deliberately not complying with the rules that have been previously socialized, the resources available to implement the Mayor Regulation are very good, but do not produce good results because there are still people who do not comply. The attitude and sense of responsibility of the Ternate City government, especially Covid-19 officers, are very good, but the attitude of the community towards the Covid-19 task force officers and towards Ternate Mayor Regulation No. 7 of 2020 is still very poor. This shows that the poor implementation of Ternate Mayoral Regulation No. 7 of 2020 is due to the fact that the support and sense of obedience of the community is still very minimal (very lacking)